AKULTURASI BUDAYA ISLAM LOKAL (Studi Perbandingan Islam di India, Afrika, Indonesia, dan Balkan) - Akhmad Satori (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
This paper seeks to provide a picture of how the acculturation process that takes place between Islam and other cultures and how far the Islamic culture influenced the local culture The focus of this paper is a cultural comparative study between India, Africa, Indonesia and the culture of the Balkans.